Pendidikan Karakter Di Lembaga Pendidikan Islam (Studi Kasus Tentang Implementasi Pendidikan Karakter Di Mtsn Ponorogo Dan Mts Ma’arif 1 Ponorogo) - Nanik Setyowati (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Character building is a very important part of national education goals. As stated in the law no. 20 of 2003 on the national education system which states that the purpose of national education is to develop the potential of learners to become human beings who believe and piety to God Almighty, noble character, healthy knowledgeable, capable, creative, independent and become citizens of democratic and to be responsible. And one of the researchers' concerns in this context is to try to discuss the implementation of character education in educational institutions, especially in the madrasah. The research methodology used a qualitative approach. Data collection using interview methods and snowball sampling, observation, and documentation techniques. Sources of data in this study were Madrasah Principals, teachers and students in both research objects. Data analysis techniques are data reduction that has been obtained then presented / in the form of display data, and the conclusion or verification. The thinking model used is inductive. The location of the research is in MTsN. Ponorogo and MTs Ma'arif 1 Ponorogo. From the results of the study found that (1) Implementation of character education in MTsN Ponorogo and MTs Ma'arif 1 Ponorogo has been formulated in vision and mission of Madrasah. (2) The efforts of MTsN Ponorogo and MTs. Ma'arif 1 Ponorogo in developing character education is designing activities that terms with the values ​​of character and build madrasah culture. (3) Characteristic implementation of character education in MTsN Ponorogo is to maximize the role of Counseling Guidance (BK) in instilling character in students. While in MTs Ma'arif 1 Ponorogo Implementation of character education is deliberately designed through the development of madrasah culture with the management of all components in Madrasah.